ROLES OF THE C-REACTIVE PROTEIN-ALBUMIN-LYMPHOCYTE INDEX AND PAN-IMMUNE-INFLAMMATION VALUE INDICES AS NEW INDICATORS OF DEMENTIA SEVERITY - Sabaz Karakeci, Emel; Aydogdu, Nesibe; Dogan, Serpil (Turkish Geriatrics Soc, 2026)
Introduction: Alzheimer's disease is a common condition that can be challenging to diagnose, primarily due to the high costs and limited availability of specific tests. This study aimed to explore the relationship between peripheral inflammation markers, such as pan-immune-inflammation-value and the C-reactive protein-albumin-lymphocyte and their ability to predict the severity of the disease. Materials and Method: Atotal of 232 patients diagnosed with Alzheimer'stype dementia and 52 healthy individuals with no history of the disease were retrospectively included in the study conducted between January 2024 and November 2025. The patients were classified into five groups based on the Clinical Dementia Rating Scale. After a 10-12 hour fast, venous blood samples were collected from all participants, and demographic and clinical data were obtained from the hospital information system. The analysis included complete blood count parameters (leukocytes, neutrophils, lymphocytes, monocytes, and platelets), C-reactive protein levels, serum albumin levels, and routine biochemical parameters from the blood samples. Results: Although there was no significant difference in pan-immune-inflammation values between the study groups (p = 0.721), the C-reactive protein-albumin-lymphocyte index showed a significant decrease as the severity of dementia increased. Similarly, Albumin-Lymphocyte Ratio, Systemic Inflammatory Index, Neutrophil-Lymphocyte Ratio, and Platelet-Lymphocyte Ratio also showed significant differences between the groups (p < 0.05). Conclusion: The findings of this study highlight the attractiveness of the C-reactive protein-albumin-lymphocyte index and the albumin/lymphocyte ratio as potential screening tools for dementia risk assessment in clinical settings.
Keywords: Biomarkers; C-Reactive Protein; Lymphocytes; Prognosis; Dementia; Inflammation; Retrospective Studies